Profesionalisme Guru Adabul ‘Alim wal Muta’allim dalam Membina Akhlak Santri Madrasah Diniyah Jabal Nur Beji - Muchammad Lubbil Khobir (Lembaga Yasin AlSys, 2026)
Although the problem of moral decline among students has been widely studied, research that specifically integrates teacher professionalism with the values of Adabul ‘Alim wal Muta’allim remains limited. This study aims to analyze the role of teacher professionalism in fostering the moral character of students at Madrasah Diniyah Jabal Nur Beji, Pasuruan. This study employed a qualitative approach with a case study design involving teachers, administrators, and students selected through purposive sampling and snowball sampling techniques. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results showed that teacher professionalism was reflected in pedagogical competence, personality, understanding of student character, lesson planning, as well as the dominant use of role-modeling and habituation methods. The development of moral character was carried out systematically through supervision, the imposition of sanctions, and rewards. These findings affirm the importance of teacher professionalism grounded in adab in character education and contribute to strengthening teacher competence and creating an educational environment that supports the moral formation of students.